Vector Superstrata - Nejc Čeplak (Journal of High Energy Physics, 2023)
Abstract We present the construction of several microstate geometries of the supersymmetric D1-D5-P black hole in which, within six-dimensional supergravity, the momentum charge is carried by a vector field. The fully backreacted geometries are smooth and horizonless: they are asymptotically AdS3 × S 3 with an AdS2 throat that smoothly caps off. We propose a holographic dual for these bulk solutions and discuss their extension to asymptotically flat space. In addition, we present several uplifts of the full six-dimensional supersymmetric ansatz to ten-dimensions. In particular, we show that there exists a frame in which geometries based on vector field momentum carriers are entirely in the NS-NS sector, making them possible starting points for the exploration of stringy black-hole microstates.